Strength in Numbers: A Model for Undergraduate Research Training and Education in the Social and Behavioral Sciences. Issue 4 (1st October 2016) - Martin, Yolanda C.; Marcus, Anthony; Curtis, Richard; Eichenbaum, Joshua; Drucker, Ernest
Abstract : This study describes a new approach to undergraduate science training that offers an alternate model to the national objective of scaling up scientific research interests and capabilities among undergraduate students. With this new focus, we seek to more effectively bring scientific research methods and experiences to larger numbers of students in non-elite educational circumstances. Our model has been designed and implemented, at the John Jay College and the Borough of Manhattan Community College, both of which are part of the City University of New York (CUNY), where we have a majority non-White and economically disadvantaged student body. We have successfully engaged large numbers of undergraduate students by linking multiple classes in the social and behavioral sciences to build collective cross-disciplinary research projects that give every enrolled student an opportunity to receive high-quality research training and create cumulative data sets over years that are cumulative, collaborative, and of professional value.